2016
DOI: 10.1152/ajpheart.00974.2015
|View full text |Cite
|
Sign up to set email alerts
|

The mechano-gated channel inhibitor GsMTx4 reduces the exercise pressor reflex in rats with ligated femoral arteries

Abstract: Mechanical and metabolic stimuli arising from contracting muscles evoke the exercise pressor reflex. This reflex is greater in a rat model of simulated peripheral arterial disease in which a femoral artery is chronically ligated than it is in rats with freely perfused femoral arteries. The role played by the mechanically sensitive component of the exaggerated exercise pressor reflex in ligated rats is unknown. We tested the hypothesis that the mechano-gated channel inhibitor GsMTx4, a relatively selective inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 48 publications
3
40
0
Order By: Relevance
“…The mechanically-sensitive component of the exercise pressor reflex during dynamic muscle contractions was found recently to be exaggerated when evoked from a previously ligated hindlimb compared to the reflex evoked from a freely perfused hindlimb (12). That investigation was designed specifically to gain translational mechanistic insights into the larger increases in blood pressure found in PAD patients versus aged-matched healthy counterparts during low-intensity rhythmic plantar flexion exercise (31,39,40), and low-intensity treadmill walking (5, 7).…”
Section: Chapter 4 -Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The mechanically-sensitive component of the exercise pressor reflex during dynamic muscle contractions was found recently to be exaggerated when evoked from a previously ligated hindlimb compared to the reflex evoked from a freely perfused hindlimb (12). That investigation was designed specifically to gain translational mechanistic insights into the larger increases in blood pressure found in PAD patients versus aged-matched healthy counterparts during low-intensity rhythmic plantar flexion exercise (31,39,40), and low-intensity treadmill walking (5, 7).…”
Section: Chapter 4 -Discussionmentioning
confidence: 99%
“…Copp et al (12) found recently that the mechanically-sensitive component of the exercise pressor reflex was exaggerated in rats with a ligated femoral artery compared to that found in rats with freely perfused femoral arteries. Specifically, GsMTx4, a relatively selective antagonist for mechano-gated piezo channels (2,6), reduced the pressor and renal sympathetic nerve responses during dynamic hindlimb muscle contraction to a greater extent in "ligated" versus "freely perfused" rats (12).…”
Section: Chapter 1 -Introductionmentioning
confidence: 90%
See 3 more Smart Citations